2022
DOI: 10.3102/00028312221075068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early College Opportunities on English Learners

Abstract: Research shows that Early College high schools have a significant impact on high school and college outcomes for students from low income and racial/ethnic minority backgrounds, but how similar opportunities extend to English learners (ELs) remains unknown. We examine a program that offers Early College opportunities in high schools serving large EL populations in California. Leveraging an exogenous policy change and rich administrative records, we look at the outcomes of pre- and postprogram cohorts of ELs (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Male DE participants have a smaller increased probability of attending a four-year college than female DE participants. This warrants further analysis as other recent scholarship has found that early college programs for English language learners reduce a student's probability of enrolling in a four-year college (A Johnson & Mercado-Garcia, 2022)…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Male DE participants have a smaller increased probability of attending a four-year college than female DE participants. This warrants further analysis as other recent scholarship has found that early college programs for English language learners reduce a student's probability of enrolling in a four-year college (A Johnson & Mercado-Garcia, 2022)…”
mentioning
confidence: 86%
“…Emerging research on early college programs designed for English language learners also indicates that these DE participants have a reduced probability of enrolling in a four-year college after high school graduation (A. Johnson & Mercado-Garcia, 2022). Thus, these outcomes are not consistent for all students -especially those who have been historically marginalized in and by educational systems.…”
Section: Social Outcomes De Varies From Other Credit-bearing Transiti...mentioning
confidence: 99%
See 2 more Smart Citations